PENERAPAN MODEL PSYCHOLOGICAL WELL-BEING KEPADA PARA PURNA GURU SMP DI KOTA CIMAHI JAWA BARAT DALAM UPAYA MENUMBUHKAN KEBAHAGIAAN DAN RASA BANGGA TERHADAP ALUMNINYA - Darmawan Yudhanegara; Pandena Kicky Basuki Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
ABSTRACT Â Community service activities by applying the Psychological Well-Being (PWB) model to former SMPN X retired teachers in Cimahi city, West Java, in an effort to foster happiness and pride in their alumni, which is carried out through a counseling process. The purpose of this activity is to foster a sense of happiness and pride for the retired teachers towards the Alumni.The implementation method used is the display and lecture method. Activities are carried out face-to-face to them from five act-driver are academian, doctors, and psychologist. The number of retired teachers that we provide counseling is as many as 17 retired teachers. The activity process starts from planning activities, giving invitations, welcoming, providing counseling and alumni appearances, providing basic necessities, closing and evaluating activities. During the process, the event that most attracted the attention of the post-teacher was the introduction and appearance of successful career people and showing that the knowledge received during junior high school was very useful in their career life. The Psychological Well-Being model is a packaging for material and how to treat life in life, how to accept life, think positively towards other former teachers, increase the value of their lives, aim and purpose in life at the end of retirement, and adapt to the surrounding environment.